Create War card game in Android Studio : create the popular War card game for Android. (Apress, 2023)
In the video, you will learn how to build the classic War card game for Android. The game is played with a full deck of 52 cards. The players play cards one by one and the bigger card gets the smaller one. The point of the game is to win all of the cards. In this game, the user will be able to play vs device. This video is a valuable resource for developers looking to grasp the fundamentals of creating Android games with Java. It covers various aspects, including game design, creating a deck of cards, playing cards on the table, and delving into the intricacies of card games. What You'll Learn How to create Android games with Java How to create game design How to write the logic for card dealing How to play cards one by one and challenge the device Who This Video Is For People with more advanced skills in Android and Java are targeted but the video will be useful for total beginners as well.